Association of GRACE Risk Score with Angiographic Severity of Coronary Artery Disease in Patients with Non ST-elevation Acute Coronary Syndrome - Rahman, Md Estakur; Mohammad Safiuddin, -; Habib, SM Ahsan; Ahmed, Chaudhury Meshkat; Banerjee, Sajal Krishna (University Heart Journal, 2020)
Background: Due to the wide spectrum of risk for death and recurrent events among patients with NSTE-ACS, management guidelines emphasise the importance of early risk stratification. In addition to prognostic assessment, predicting the anatomical extension of coronary artery disease is potentially useful for clinical decision. The aim of the study is to determine whether the GRACE risk score correlates with the angiographic extent and severity of coronary artery disease in patients with non ST-elevation ACS Methods: A total of 50 patients with non-ST-elevation acute coronary syndrome were enrolled to the study. Based on the GRACE risk score classification system, the patients were divided into low (<108), intermediate (109-140), and high (>140) risk groups. All patients underwent coronary angiography within five days after admission. The severity of the coronary artery disease was assessed by Gensini score. Relation between Grace score and Gensini score was evaluated. Results: Mean Gensini score were 12.20 ± 13.60, 34.52 ± 13.50 and 48.41 ± 14.56 in low group, intermediate group and high GRACE risk group respectively and the difference of mean Gensini score was statistically significant (p<0.001). A GRACE score of 135 was identified as the optimal cut-off to predict severe CAD (sensitivity = 82.4% and specificity = 75.8%). In our study correlation co-efficient between GRACE risk score and Gensini score was r=0.66 (p<0.001). Conclusion: The study demonstrates that the GRACE risk score has significant positive correlation with coronary artery stenosis in patients with non-ST-elevation acute coronary syndrome. University Heart Journal Vol. 17, No. 1, Jan 2021; 38-41